ProLaw: ethical software aid for legal professionals - Silva, André Tadeu Reis e (2018)
A considerable part of legal professionals’ time is spent researching and analyzing legislation, both in force and to be approved, court decisions, new trends in law, among others. Tasks such as these are a never-ending process, as Portuguese laws and European directives and regulations, as well as new court decisions and interpretations of the law are issued daily and leave less time for other tasks such as drafting contracts and court briefs and petitions, evaluating a client’s legal situation or even obtaining new clients. As such, in the wake of artificial intelligence developments, there is room for a technological solution to assist in all legal research and analysis tasks. Instead of researching each information required through long public (or private) databases, ProLaw technology will provide real-time inputs as someone is writing a legal document. Another goal is that legal professionals redirect a part of the time saved by applying the software in pro bono cases, which could involve litigation or general legal assistance. The main goal of this business plan is to take advantage of two market gaps, one in the legal industry and the other one in social service, by providing a uniform solution. This will allow two completely separated environments to unite by exchanging assistance, knowledge, experiences and, potentially, enabling young and less resourceful generations to reach higher levels of knowledge and wealth.